Sennacherib's Campaign Against Judah and Jerusalem in 701 B.C.: A Historical Reconstruction - Matty, Nazek Khalid (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2016)
This study offers a reconstruction of Sennacherib’s campaign against Judah and Jerusalem in 701 BC. It contrasts and compares various, partly contradictious readings of this event and challenges established narratives. By giving equal weight to a great variety of different sources, whether literary or archaeological, the author comes to a new and profound understanding of this complex military conflict.